Sistem Penentuan Paket Penjualan dengan Algoritma FP-Growth Serta Metode Up dan Cross Selling - Febriantho Febriantho; Samidi Samidi; Gregorius Mikael; Endang Saputra (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The Car Spare Part Shop is one of the Car Spare Parts Shops in Tangerang Regency. Based on interviews conducted with shop owners at the Car Spare Parts Store, it was stated that there was a decrease in sales income every month, so there was limited capital in purchasing car spare parts products which resulted in difficulties in choosing which car spare parts products to order. The purpose of this study is to create a system to process and utilize sales transaction data using the FP-Growth algorithm as well as up selling and cross selling methods which will later be used to sell car spare parts that are purchased simultaneously in a sales package determination system. The sales transaction data used is 6,674 transaction data for 1 year of operation of the Car Spare Part Shop (July 2021 - June 2022) with 30,956 records in Microsoft Excel format. The prototype system uses the Python framework flask and mysql database. Validation test results ensure that the software that has been made is in accordance with the expected functional requirements specifications. The results of the system quality test with ISO 9126 can be concluded in the criteria of Very Good with a value of 98.59%. With the results of the Functionality aspect of 99.25%, the results of the Reliability aspect of 98.13%, the results of the Usability aspect of 98.33% and the results of the Efficiency aspect of 98.66%. The results of system security testing with Acunetix and LOIC software have been carried out and the system is still stable and the system is declared safe when used.